ANALYSIS OF THE APPLICATION OF PASSIVE PROTECTION AND FIRE MANAGEMENT SYSTEMS IN THE FACULTY OF ECONOMICS AND BUSINESS BUILDING UPN VETERAN JAKARTA YEAR 2020 - Napitupulu, Caroline Atari (Universitas Pembangunan Nasional Veteran Jakarta, 2020)
Background: The Faculty of Economics and Business Building UPN Veteran Jakarta has two different buildings, the Muh. Husni Thamrin and the Soepomo Building. The purpose of this study was to analyze the appropriateness of the application of passive protection, life-saving, organizing, and fire prevention systems at the Faculty of Economics and Business Building, UPN Veteran Jakarta with the applicable regulatory standards. Methods: This study uses qualitative research and descriptive research design with direct observation and interview methods. The results of this study were compared in accordance with Peraturan Daerah Provinsi DKI Jakarta Nomor 8 Tahun 2008, Peraturan Menteri Pekerjaan Umum Nomor 20/PRT/M/2009, Peraturan Menteri Pekerjaan Umum Nomor 26/PRT/M/2008, NFPA 101 and NFPA 220 as a comparison. Result: The results of this study found that the organization in FEB was not up to standard due to the absence of an emergency response team and the absence of a fire protection organization. Conclusion: The conclusion of this research about organizing at FEB UPN Veteran Jakarta is not in accordance with the standards. FEB needs to create an emergency response team and fire protection organization.